Optimizing sparse RFI prediction using deep learning. Issue 2 (8th July 2019) - Kerrigan, Joshua; Plante, Paul La; Kohn, Saul; Pober, Jonathan C; Aguirre, James; Abdurashidova, Zara; Alexander, Paul; Ali, Zaki S; Balfour, Yanga; Beardsley, Adam P; Bernardi, Gianni; Bowman, Judd D; et al.
ABSTRACT: Radio frequency interference (RFI) is an ever-present limiting factor among radio telescopes even in the most remote observing locations. When looking to retain the maximum amount of sensitivity and reduce contamination for Epoch of Reionization studies, the identification and removal of RFI is especially important. In addition to improved RFI identification, we must also take into account computational efficiency of the RFI-Identification algorithm as radio interferometer arrays such as the Hydrogen Epoch of Reionization Array (HERA) grow larger in number of receivers. To address this, we present a deep fully convolutional neural network (DFCN) that is comprehensive in its use of interferometric data, where both amplitude and phase information are used jointly for identifying RFI. We train the network using simulated HERA visibilities containing mock RFI, yielding a known 'ground truth' data set for evaluating the accuracy of various RFI algorithms. Evaluation of the DFCN model is performed on observations from the 67 dish build-out, HERA-67, and achieves a data throughput of 1.6 × 10 5 HERA time-ordered 1024 channelled visibilities per hour per GPU. We determine that relative to an amplitude only network including visibility phase adds important adjacent time–frequency context which increases discrimination between RFI and non-RFI. The inclusion of phase when predicting achieves a recall of 0.81, precision of 0.58, and F 2 score of 0.75 as applied to our HERA-67 observations.